Paradoxical Features of Primary Shear Fractures and General Faults - Tarasov, B.G.; Randolph, M.F. (Deep Mining 2007: Proceedings of the Fourth International Seminar on Deep and High Stress Mining, 2007)
This paper shows that hard rocks exhibit specific properties at high confining pressure that distinguish them markedly from common rock behaviour: they become extremely brittle and lose shear resistance within a certain range of shear rupture displacement. The combination of these two features results in increasing instability with depth and makes rupture abnormally violent, both of which are well established experimentally from studies of earthquakes and rock bursts at high stress levels. The behaviour is caused by the intrinsic nature of the fault structure, which is an echelon of blocks operating as hinges, essentially eliminating friction at high confining pressure of a certain displacement range. The paper demonstrates that, while the same structure may be found at different scale in primary fractures and general faults, significantly different mechanisms are responsible for the formation of the structure in each case. A new approach is proposed for understanding fault segmentation and the role of junctions in fault propagation. It is argued that segmentation is a result of advanced triggering of new fractures that propagate both towards the current fracture and in the opposite direction. This mechanism triples the fault propagation speed. Junctions formed at the meeting of the approaching segments help to accommodate the fault displacement and can significantly decrease the fault strength - thus contradicting the general belief that junctions represent strength barriers impeding the fault motion. The improved understanding of the fracture process is important for better prediction and mitigation of dynamic events such as earthquakes and rock bursts.